BUDAYA PESANTREN DAN PENDIDIKAN KARAKTER PADA PONDOK PESANTREN SALAF - M. Syaifuddien Zuhriy (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
As part of the community, pesantren with typical of the main elements such as kiai, santri, mosque, cottage and classical instruction books (kitab kuning), has become its own subculture. Therefore, despite modernization and globalization invaded, pesantren can still maintain its existence. Furthermore, many stakeholders indicated that the pesantren are educational institutions that can serve as a model of character education in Indonesia. How the strategies and patterns of character education by pesantren so as to create culture? What are these cultures? These are the two main questions are answered through qualitative research is in pesantren Langitan, Tuban and pesantren Ihyaul Ulum, Gilang.